Assessing the reclamation of a contaminated site affected by the Fundão dam tailings trough phytoremediation and bioremediation - Rondina Gomes, Alessandra; Antão, Arthur; Santos, Carlos Henrique [UNESP]; Rigobelo, Everlon C. [UNESP]; Scotti, Maria Rita (Taylor & Francis, 2024)
The rupture of the Fundão dam (Brazil) spread tailings contaminated with sodium and ether-amine into the Doce River Basin. Aiming at rehabilitating a contaminated riparian site, phytoremediation with native species of the Atlantic Forest was performed under four treatments: ES-1: physical remediation (sediment scraping) + chemical remediation (organic matter) + bioremediation (double inoculation with the arbuscular mycorrhizal fungus (AMF) Rhizophagus irregularis and the plant growth-promoting bacteria Bacillus subtilis); ES-2: chemical remediation + bioremediation; ES-3: physical remediation + chemical remediation; ES-4: chemical remediation. Ether-amine and sodium contents, plant growth and, soil quality parameters were compared among treatments and relative to preserved and degraded sites. Two years after planting, the outstanding plant growth was attributed to the phytoremediation of ether-amine and ammonium, followed by a significant increase in soil microbial biomass (Phospholipid fatty acids-PLFAs), particularly the Gram+ bacteria and total fungi but not AMF, whose response was independent of the inoculation. While sodium and ether-amine declined, soil K, P, NO3− contents, dehydrogenase and acid phosphatase activities, cation exchange capacity (CEC) and soil aggregation increased, especially in ES-1. Thus, such remediation procedures are recommended for the restoration of riparian areas affected by the Fundão tailings, ultimately improving sediment fertility, aggregation and stabilization.
Keywords: Acid phosphatase; Bacillus; ether-amine; land restoration; phospholipid fatty acids; sodium